Exon skipping for Duchenne muscular dystrophy: a systematic review and meta-analysis - Yuko Shimizu-Motohashi; Terumi Murakami; En Kimura; Hirofumi Komaki; Norio Watanabe (Orphanet Journal of Rare Diseases, 2018)
Abstract Background Exon skipping has been considered a promising therapeutic approach for Duchenne muscular dystrophy (DMD). Eteplirsen received conditional approval in the United States in 2016. To date, no systematic reviews or meta-analyses of randomized controlled trials (RCTs) of exon skipping drugs have been published to determine the pooled estimates for the effect of exon skipping in treating DMD. Methods A systematic review and meta-analysis of double-blind RCTs comparing exon-skipping drugs with placebo in DMD was performed. Trials were identified by searching published and unpublished studies from electronically available databases and clinical trial registries through October 2017. The primary outcomes were changes in the 6-min walk test (6MWT) distance, North Star Ambulatory Assessment (NSAA) scores, and adverse events. Random-effects meta-analysis and assessment of risk of bias were performed. This systematic review was registered at PROSPERO (CRD42016037504). Results Five studies involving 322 participants were included, investigating eteplirsen in one and drisapersen in four studies. There were no changes in 6MWT distance (mean difference [MD] − 9.16, 95% confidence interval [CI] − 21.94 to 3.62) or NSAA scores (MD 1.20, 95% CI − 2.35 to 4.75) after 24 weeks of treatment in the exon-skipping group compared with placebo. Subgroup analysis for a 6 mg/kg weekly injection of drisapersen showed significant changes in the 6MWT, favoring drisapersen after 24 weeks (MD − 20.24; 95% CI − 39.59 to − 0.89). However, drisapersen resulted in a significant increase in injection site reactions (risk ratio [RR] 3.67, 95% CI 1.96 to 6.89, p < 0.0001) and renal toxicity (RR 1.81, 95% CI 1.11 to 2.94, p = 0.02). Risk of bias was high in two of the five studies, including the eteplirsen and one drisapersen study. Conclusions Current available data do not show evidence that exon-skipping drugs are effective in DMD. Despite potential effectiveness when used at a specific dose, significant side effects were reported with drisapersen. The small number of RCTs with relatively small numbers of participants indicate the difficulty in conducting sufficiently powered studies of DMD. Prospectively planned meta-analysis and utilization of the real-world data may provide a more precise estimate of the effect of exon skipping in this disease.